Cleaning and microstructural effects of amyl acetate on pulp chamber dentin impregnated with epoxy resin-based endodontic sealer - Zaniboni, Joissi Ferrari [UNESP]; de Souza, Vitor [UNESP]; Escalante-Otárola, Wilfredo Gustavo; Leandrin, Thaís Piragine [UNESP]; Fernández Godoy, Eduardo; Besegato, João Felipe; Kuga, Milton Carlos [UNESP] (Wiley, 2022)
Objective: To evaluate the cleaning potential of 95% ethanol, acetone, and amyl acetate solutions used solely or in association, to remove epoxy resin-based sealer residues from pulp chamber dentin and their microstructural effects. Materials and Methods: One hundred and eighty bovine incisor specimens were divided into nine groups according to the cleaning protocol: ET (ethanol); AC (acetone); AA (amyl acetate); E1: AA+AC; E2: AA+ET; E3: AC+ET; E4: AA+AC+ET; PC (positive control), and NC (negative control). All groups were impregnated with epoxy resin-sealer, except NC. Ninety specimens were divided into groups (n = 10) for evaluation of persistence of residues and amount of open dentinal tubules by SEM analysis and evaluation of chemical compounds on the dentin surface after cleaning with electron dispersive spectroscopy. The others 90 specimens were submitted to Knoop microhardness evaluation. Persistence of residues data were submitted to the Kruskal Wallis and Dunn tests (α = 0.05). Open dentinal tubules and microhardness data were submitted to one-way ANOVA and Mann Whitney tests (α = 0.05). Results: AA and E4 protocols showed the lowest persistence of residues. E4 group had the highest incidence of open dentinal tubules. E3 and E4 groups showed no changes in the atomic ratio Ca/P, which was similar to NC group. E4 group did not present W, an element presents in all the other groups. ET and E4 protocols showed the smallest reduction in dentin microhardness. Conclusions: The combination of amyl acetate, acetone and ethanol is the most effective and safe protocol to remove epoxy sealer residues on pulp chamber dentin. Moreover, it has the lowest microhardness reduction. Clinical Significance: The combined use of amyl acetate, acetone, and ethanol enhanced the cleaning of pulp chamber dentin with minimal microstructural damage.
Keywords: amyl acetate; epoxy resin sealer; root canal sealer; xylol